Colloidal Sol–Gel Synthesis and Photocatalytic Activity of Nanoparticulate Nb2O5 Sols. Issue 6 (22nd March 2016) - Falk, Gilberto; Borlaf, Mario; Bendo, Tatiana; Novaes de Oliveira, Antonio Pedro; Rodrigues Neto, João Batista; Moreno, Rodrigo
Abstract : A detailed study of a novel synthesis via colloidal sol–gel route for obtaining nanoparticulate Nb2 O5 was performed. Parameters such as temperature and H + :Nb 5+ and Nb 5+ :H2 O molar ratios were controlled in order to determine the best conditions of synthesis. Moreover, particle size distribution, zeta potential, structure by X‐ray diffraction, and the photocatalytic activity of the particulate sols were also evaluated. The obtained results indicate that the colloidal sol–gel synthesis is a good alternative for obtaining Nb2 O5 either as stable nanoparticulate sol or as a nanosized powder. Nb2 O5 amorphous nanoparticles with an average size of 20 nm were obtained by controlling the synthesis variables. The heat‐treatment process allowed the formation of Nb2 O5 with orthorhombic structure that transforms at higher temperatures to monoclinic phase. The highest photocatalytic activity was observed under λ = 365 nm, the smallest UV energy used in the experimental tests.